Gender Gap in Neurology Research Authorship (1946–2020) - Nguyen, Anne X.; Yoffe, Lilian; Li, Anna; Trinh, Xuan-Vi; Kurian, Jerry; Moss, Heather E.; Wu, Albert Y. (Frontiers in Neurology, 2021)
Gender disparity in the field of neurology impedes scientific advancements and innovations. In 2018, 45.0% of neurology and neurological subspecialty residents were women. Despite a notable rise in the proportion of women neurologists over the past decades, inequalities regarding publication proportions between men and women persist in the field. This cohort study examines authorship trends in articles published in 155 international neurology journals, identified as those listed in the annual Journal Citation Reports' “Clinical Neurology” section. Authors' names, authorship positions and countries of affiliation were extracted from PubMed for indexed articles published from 1946 to 2020. Gender-API (a validated and highly accurate application program interface) assigned binary genders to authors. Author gender proportions were compared across subspecialties, authorship position and years. In 303,385 unique articles, 1,663,036 total authors were identified of which 34.1% were women. Neuroradiology demonstrated the lowest proportion of women authors (21.3%), while neurogenetics displayed the highest (44.5%). In articles with multiple authors, both men and women last authors were more likely to publish with a male first author, though this was significantly more pronounced for men last authors (1.86 vs. 1.08; p < 0.001). From 2002 to 2020, women remained in the minority of last (24.6%), first (36.2%), and middle author positions (35.8%). The authorship gender distribution in neurological journals neither reflects the gender proportion of neurologists in the field overall nor in any subspecialty examined. We also find a tendency for senior and junior authors of the same gender to publish together which perpetuates authorship inequity. Further work is needed to identify underlying causes so that interventions might be developed to improve authorship diversity.